2004
DOI: 10.1007/s00775-004-0536-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction kinetics of the copper-responsive CopY repressor with the cop promoter of Enterococcus hirae

Abstract: In Enterococcus hirae,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
0
51
0
Order By: Relevance
“…Interestingly, there is a perfect cop box upstream of the proposed GGAG ribosome binding site. cop boxes are short, inverted repeats of sequence motif TACAnn TGTA and are the consensus binding motif of CopY-type repressors of firmicutes (16,17). CopY-type repressors are copper inducible and regulate the expression of the copper ATPases in Enterococcus hirae (26) and L. lactis (17) and probably also in related bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there is a perfect cop box upstream of the proposed GGAG ribosome binding site. cop boxes are short, inverted repeats of sequence motif TACAnn TGTA and are the consensus binding motif of CopY-type repressors of firmicutes (16,17). CopY-type repressors are copper inducible and regulate the expression of the copper ATPases in Enterococcus hirae (26) and L. lactis (17) and probably also in related bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…When cytoplasmic copper becomes excessive, the zinc ion of CopY is replaced by two Cu ϩ ions to form Cu ϩ 2 -CopY, which is released from the DNA and allows transcription of the downstream genes to proceed (1,2). CopY-type repressors are ubiquitous in firmicutes and we have previously shown that the purified CopY-type repressors of Enterococcus hirae, Streptococcus mutans, and L. lactis all bind to the same cop box-containing promoters with similar affinity and that binding is abolished by copper (16,17). In agreement with this general concept, purified CopR of L. lactis was found to bind to the cop box present in the promoter region of the lctO gene, and this interaction was abolished by copper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF1 encodes a predicted 227-amino-acid polypeptide with the deduced amino acid sequence of a gene product exhibiting 66 and 63% identity to CopR from P. syringae (33) and to PcoR from E. coli (12), respectively. Using primer extension, the probable transcriptional start of ORF1 was identified 57 bases upstream (G) of the predicted GTG start codon and was associated with a conserved palindrome previously identified as a copper box within copper-responsive promoters (33,34,36) (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Genes involved in copper homeostasis are best characterized in E. hirae (16,(34)(35)(36)(37)(38)(39) but have also been studied in other streptococcal organisms, including S. mutans (14,36) and S. pneumoniae (13,40). In these organisms as well as in other pathogenic bacteria, the genes are located within a cop operon and represent an important virulence mechanism (13,(18)(19)(20)(21).…”
Section: S Pyogenes Clinical Isolates Contain a Cop Operon-like Locusmentioning
confidence: 99%